Genome-Wide SNP Discovery and Population Genetic Analysis of Mesocentrotus nudus in China Seas - Wang, Quanchao; Liu, Ying; Yan, Lang; Chen, Linlin; Li, Baoquan (Frontiers in Genetics, 2021)
Mesocentrotus nudus (M. nudus) is an important commercially aquatic species because of high edible and medicinal value. However, wild stocks have dramatically decreased in recent decades. Understanding the population structure and genetic diversity can provide vital information for genetic conservation and improvement. In the present study, the Genotyping-By-Sequencing (GBS) approach was adopted to identify the genome-wide SNPs from a collection of 80 individuals consisting of five geographical populations (16 individuals from each population), covering the natural habitats of M. nudus in China seas. An average of 0.96 Gb clean reads per sample were sequenced, and a total of 51 738 biallelic SNPs were identified. Based on these SNPs, diversity index analysis showed that all populations have similar pattern with positive Fis (0.136) and low Ne (724.3). Low genetic differentiation and high genetic connectivity among five geographical populations were detected by pairwise Fst, PCA, admixture and phylogenetic analysis. Besides, two YWL individuals originating from an isolated ancestor may imply that there is a genetically differentiated population in adjacent sea. Overall, the results showed that the GBS is an effective method to detect genome-wide SNPs for M. nudus, and suggested that the protective measures and the investigation with larger spatial scale and sample size for M. nudus should be carried out in the future.